Participate in physical education preferences of boys and girls of secondary education through "the GR level of social participation in learning" - Luis Miguel Ruiz Pérez; José Luis Graupera Sanz; Isabel Rico Sánchez; Esmeralda Mata (Asociación Española de Ciencias del Deporte, 2010)
This investigation is concerned with the analysis of interaction preferences among secondary school children in physical education. 6.263 secondary school children participated in this study and completedthe Social Participation in Learning Scale (GR). Psychometric properties were re-evaluated and it wasanalyzed gender differences in the four dimensions of this scale: Cooperative dimension, Competitive dimension, Affiliative dimension and Individualistic dimension. The results showed that, in general,secondary school children think that they are cooperative, in reference to gender; boys got higher scoresin the competitive and individualistic dimensions and girls in the cooperative and affiliative dimensionsof the scale. The signification of these results is analyzed. KEY WORDS: Social Interaction, Gender, Assessment, Participation, Secondary physical education